THE ROLE OF THE INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) TO DECREASING A NUMBER OF CHILD SOLDIER IN SOUTH SUDAN - Nadirah (Universitas prof. Dr. Moestopo (Beragama), 2022)
This study aims to determine The Performance of the International Committee of the Red Cross. The method used in this research is a qualitative method with descriptive research type. The data collection technique used in this research is library research in the form of books, reports, journal articles and internet sites. The theory used is Diplomatic Termination Theory. In this regard, there is a role for the ICRC in reducing child soldiers in South Sudan during the 2014-2019 period, which in the eyes of international humanitarian law is illegal. This role is in the form of humanitarian programs for South Sudan which indirectly reduce the recruitment of child soldiers in South Sudan in the 2014-2019 period. The results of the study explain that in carrying out its role by reducing child soldiers in South Sudan, the ICRC has proven to play an active role and can carry out its role well.